Targeting Hsp70: A possible therapy for cancer. Issue 1 (28th April 2016) - Kumar, Sanjay; Stokes, James; Singh, Udai P.; Scissum Gunn, Karyn; Acharya, Arbind; Manne, Upender; Mishra, Manoj
Highlights: Hsp70 promotes tumor cell survival by interacting at several points in apoptotic signaling pathway(s). Interaction on different immunological and immunotherapeutic impacts of Hsp70 in cancer cell survival are summarized. Advance strategies to target Hsp70 are discussed and future directions are proposed. Hsp70 can be used as an immunotherapeutic drug because its potent adjuvant nature induces cancer autoimmunity. Abstract: In all organisms, heat-shock proteins (HSPs) provide an ancient defense system. These proteins act as molecular chaperones by assisting proper folding and refolding of misfolded proteins and aid in the elimination of old and damaged cells. HSPs include Hsp100, Hsp90, Hsp70, Hsp40, and small HSPs. Through its substrate-binding domains, Hsp70 interacts with wide spectrum of molecules, ranging from unfolded to natively folded and aggregated proteins, and provides cytoprotective role against various cellular stresses. Under pathophysiological conditions, the high expression of Hsp70 allows cells to survive with lethal injuries. Increased Hsp70, by interacting at several points on apoptotic signaling pathways, leads to inhibition of apoptosis. Elevated expression of Hsp70 in cancer cells may be responsible for tumorigenesis and for tumor progression by providing resistance to chemotherapy. In contrast, inhibition or knockdown of Hsp70 reduces the size of tumors and can cause their complete regression. Moreover, extracellular Hsp70 acts as an immunogen that participates in cross presentation of MHC-I molecules. The goals of this review are to examine the roles of Hsp70 in cancer and to present strategies targeting Hsp70 in the development of cancer therapeutics.